A Novel Synthesis of Gold Nanoparticles Supported on Hybrid Polymer/Metal Oxide as Catalysts for p-Chloronitrobenzene Hydrogenation - Cristian H. Campos; Bruno F. Urbano; Cecilia C. Torres; Joel A. Alderete (Journal of Chemistry)
This contribution reports a novel preparation of gold nanoparticles on polymer/metal oxide hybrid materials (Au/P[VBTACl]-M metal: Al, Ti or Zr) and their use as heterogeneous catalysts in liquid phase hydrogenation of p-chloronitrobenzene. The support was prepared by in situ radical polymerization/sol gel process of (4-vinyl-benzyl)trimethylammonium chloride and 3-(trimethoxysilyl)propyl methacrylate in conjunction with metal-alkoxides as metal oxide precursors. The supported catalyst was prepared by an ion exchange process using chloroauric acid (HAuCl4) as gold precursor. The support provided the appropriate environment to induce the spontaneous reduction and deposition of gold nanoparticles. The hybrid material was characterized. TEM and DRUV-vis results indicated that the gold forms spherical metallic nanoparticles and that their mean diameter increases in the sequence, Au/P[VBTACl]-Zr > Au/P[VBTACl]-Al > Au/P[VBTACl]-Ti. The reactivity of the Au catalysts toward the p-CNB hydrogenation reaction is attributed to the different particle size distributions of gold nanoparticles in the hybrid supports. The kinetic pseudo-first-order constant values for the catalysts in the hydrogenation reaction increases in the order, Au/P[VBTACl]-Al > Au/P[VBTACl]-Zr > Au/P[VBTACl]-Ti. The selectivity for all the catalytic systems was greater than 99% toward the chloroaniline target product. Finally the catalyst supported on the hybrid with Al as metal oxide could be reused at least four times without loss in activity or selectivity for the hydrogenation of p-CNB in ethanol as solvent.